On Burkholderiales order microorganisms and cystic fibrosis in Russia - Olga L. Voronina; Marina S. Kunda; Natalia N. Ryzhova; Ekaterina I. Aksenova; Natalia E. Sharapova; Andrey N. Semenov; Elena L. Amelina; Alexandr G. Chuchalin; Alexandr L. Gintsburg (BMC Genomics, 2018)
Abstract Background Microbes infecting cystic fibrosis patients’ respiratory tract are important in determining patients’ functional status. Representatives of Burkholderiales order are the most dangerous. The goal of our investigation was to reveal the diversity of Burkholderiales, define of their proportion in the microbiome of various parts of respiratory tract and determine the pathogenicity of the main representatives. Results In more than 500 cystic fibrosis patients, representing all Federal Regions of Russia, 34.0% were infected by Burkholderia cepacia complex (Bcc), 21.0% by Achromobacter spp. and 12.0% by Lautropia mirabilis. B. cenocepacia was the most numerous species among the Bcc (93.0%), and A. ruhlandii was the most numerous among Achromobacter spp. (58.0%). The most abundant genotype in Bcc was sequence type (ST) 709, and in Achromobacter spp. it was ST36. These STs constitute Russian epidemic strains. Whole genome sequencing of strains A. ruhlandii SCCH3:Ach33–1365 ST36 and B. cenocepacia GIMC4560:Bcn122 ST709 revealed huge resistomes and many virulence factors, which may explain the difficulties in eradicating these strains. An experience of less dangerous B. cenocepcia ST710 elimination was described. Massively parallel sequencing of 16S rDNA amplicons, including V1-V4 hypervariable regions, was used to definite “healthy” microbiome characteristics. Analysis of maxillary sinus lavage of 7 patients revealed infection with Proteobacteria of the same ST as pathogens from sputum, suggesting that the maxillary sinus is a source of infection in cystic fibrosis patients. Conclusions Characterization of the Russian epidemic bacterial strains in the sputum and sinuses of cystic fibrosis patients have better defined the importance of Burkholderiales bacteria. This information may aid in the development of effective approaches for treatment of this disease.